2018
DOI: 10.1124/jpet.117.244400
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Chitosan, Cellulose, and Seaweed Polysaccharide Inhibits Postoperative Intra-abdominal Adhesion in Rats

Abstract: Intra-abdominal adhesion is a common complication after laparotomy. Conventional therapeutic strategies still cannot safely and effectively prevent this disorder. In this study, a combination of chitosan, cellulose, and seaweed polysaccharide (thereafter referred as CCS) was developed to significantly alleviate the formation of postoperative adhesion in rats with abdominal trauma. Transforming growth factor 1 (TGF-1, an important promoter of fibrosis) and its downstream factors-namely, alpha-smooth muscle acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…The anti-adhesion effect of sustained-release in-domethacin membrane composed of a phospholipid and PCL blend was investigated in vivo by creating defects in both the cecum and peritoneum of rats. At the early stage after tissue injury, various proinflammatory mediators (e.g., TNF-α, TGF-β, IL-1, and IL-6) are released at the damaged peritoneum, and inflammatory responses promote tissue fibrosis (37,38). Insufficient fibrinolysis in traumatized sites results in the deposition of extracellular matrix components and the formation of fibrinogen-rich adhesion tissue (1).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-adhesion effect of sustained-release in-domethacin membrane composed of a phospholipid and PCL blend was investigated in vivo by creating defects in both the cecum and peritoneum of rats. At the early stage after tissue injury, various proinflammatory mediators (e.g., TNF-α, TGF-β, IL-1, and IL-6) are released at the damaged peritoneum, and inflammatory responses promote tissue fibrosis (37,38). Insufficient fibrinolysis in traumatized sites results in the deposition of extracellular matrix components and the formation of fibrinogen-rich adhesion tissue (1).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, biopolymers are shown to have antifibrotic and anti‐inflammatory effects. Tian et al . reported that chitosan, cellulose, and seaweed polysaccharide not only suppressed TGF‐B1 (an important promoter of fibrosis) and its downstream factors but also suppressed TAK1, JNK, SAPK, and MAPK inflammation signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…[60][61][62][63][64][65][66][67][68][69][70][71][72][73] Additionally, biopolymers are shown to have antifibrotic and anti-inflammatory effects. Tian et al 74 reported that chitosan, cellulose, and seaweed polysaccharide not only suppressed TGF-B1 (an important promoter of fibrosis) and its downstream factors but also suppressed TAK1, JNK, SAPK, and MAPK inflammation signaling pathways. These studies prove that biopolymers are safe and can be applied in low-sodium sausage manufacturing.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan-containing barriers are available as a film, gel, or combined with cellulose and seaweed polysaccharides. Several studies demonstrate that chitosan-based products decreased coverage and severity of adhesions in rabbit, porcine, and murine models in cardiac, abdominal, and gynecological surgeries [292][293][294][295][296][297][298][299]. To our knowledge, chitosan itself is yet to be employed in clinical use in humans.…”
Section: Chitosan Basedmentioning
confidence: 99%